The Capricious Nature of Theory of Mind: Does Mental State Understanding Depend on the Characteristics of the Target?. Issue 2 (30th January 2019) - Gönültaş, Seçil; Selçuk, Bilge; Slaughter, Virginia; Hunter, John A.; Ruffman, Ted
Abstract : Using a between‐groups design and random assignment, this study examined 214 Turkish children's ( M  = 11.66 years) mindreading and general reasoning about in‐group members (Turks), similar out‐group members (Syrians within Turkey) and dissimilar out‐group members (Northern Europeans). Children heard four mindreading and four general reasoning stories with in‐group or out‐group members as targets. Whereas children's general reasoning about three groups was equivalent, accuracy of mental state inferences differed by target with more accurate mindreading of in‐group targets compared to both sets of out‐group targets. In this Turkish sample, mindreading of Syrian targets was the least accurate. Prejudice and perceived realistic threat predicted lower mindreading. These findings have important implications for understanding how similarity and intergroup processes play a role in children's mindreading.